Parliamentary elections in Poland 1989—2011 - Wojtasik, Waldemar (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Parliamentary elections, which are shaping the sphere of political competition and the structure of the party system, have been held in Poland since 1989. The article shows the evolution of the system of elections to the parliament and its impact on the institutionalization of the party system. The current shape of the election system proves that the party system is stable both in terms of the sustainability of party entities and the standards of political competition in the election arena. Elections are also a factor which consolidates party leadership in the case of the major political groups. This is particularly visible after Poland’s accession to the European Union. The evolution of the process of gaining political relevance by new political parties is also observed. Following 2001, only one new political party was able to win parliamentary representation. Key words: Parliamentary elections in Poland, Polish party system, electoral competition, Donald Tusk, Jarosław Kaczyński